(untitled) (Research, Society and Development, 2020)
Kefir is a fermented milk with a mild, effervescent and low alcohol content, resulting from the fermentation of milk with grains. Babassu is well known among traditional Brazilian populations, babassu milk is a by-product of the fruit that has stood out in cooking and falls into the category of products called low acidity with a final pH above 4.6. This work aims to multiply kefir grains in babassu coconut milk, associating the fruit’s characteristics with its functional properties, enhancing nutritionally. This is an experimental, observational, descriptive and quantitative study. Adaptation processing was carried out at room temperature in a solution containing 100 ml of the babassu milk vegetable extract and the whole milk with a solution change in a twenty-four hour interval. The production of babassu milk kefir follows the traditional method of whole milk (UHT), with some modifications being continued. Dewatering was done to separate the yogurt and whey. Babassu coconut milk yogurt has a grainy texture as it contains a little bit of the babassu almond crushing fiber, has a coconut odor, more oily due to the almonds. Thus, it was possible to observe the multiplication of grains in the substrate of babassu coconut milk, optimizing this probiotic to improve intestinal health and increase the absorption of nutrients.